(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
The aim of this paper is to propose a model that allows to design and build an intelligent type of organization in the field of agricultural research from how the role of the top management should be applied, and from the articulation of two management approaches. The idea of this model is to propose a transformation of the structure and culture of these institutions in a space created to facilitate the processes and procedures to enhance the exploitation of its intellect, to generate products and services in areas of clear value added for the sector linked to them, in order to satisfy the requirements of the agro-food population from an orientation based on sustainability. The proposal is based on a document review under an analysis of discrepancy of reality, applying aspects of the theories and empirical observations on the management of knowledge as a structural platform, and organizational development as a tool for managing, adapting them to the characteristics of the object of study. It combines elements of both approaches in order to contribute to the understanding of how the top management must lead the processes of transformation and translation of this proposal on the basis of two fundamental assets of the company: human capital and innovation